2013
DOI: 10.1186/1471-230x-13-67
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver FGF21 in hepatocarcinogenesis and during hepatic stress

Abstract: BackgroundFGF21 is a promising intervention therapy for metabolic diseases as fatty liver, obesity and diabetes. Recent results suggest that FGF21 is highly expressed in hepatocytes under metabolic stress caused by starvation, hepatosteatosis, obesity and diabetes. Hepatic FGF21 elicits metabolic benefits by targeting adipocytes of the peripheral adipose tissue through the transmembrane FGFR1-KLB complex. Ablation of adipose FGFR1 resulted in increased hepatosteatosis under starvation conditions and abrogation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 62 publications
(98 reference statements)
5
97
1
3
Order By: Relevance
“…29,30 We found that S-FGF21 correlated with prohormone brain natriuretic peptide and ejection fraction %, suggesting that heart failure could induce FGF21. Despite reports of increased expression of FGF21 in the liver in hepatic stress and hepatocarcinogenesis in mice and humans, 31 we found no S-FGF21 increase in liver pathology (mCRC, PBC, PSC), nor did it associate with liver dysfunction tests or degree of atypia in biliary tracts, indicating that FGF21 is not a general consequence of liver disease. Poor disease prognosis or general frailty did not stimulate S-FGF21.…”
Section: Discontinuation Of Statin Treatment and Clinical Remission Ocontrasting
confidence: 99%
“…29,30 We found that S-FGF21 correlated with prohormone brain natriuretic peptide and ejection fraction %, suggesting that heart failure could induce FGF21. Despite reports of increased expression of FGF21 in the liver in hepatic stress and hepatocarcinogenesis in mice and humans, 31 we found no S-FGF21 increase in liver pathology (mCRC, PBC, PSC), nor did it associate with liver dysfunction tests or degree of atypia in biliary tracts, indicating that FGF21 is not a general consequence of liver disease. Poor disease prognosis or general frailty did not stimulate S-FGF21.…”
Section: Discontinuation Of Statin Treatment and Clinical Remission Ocontrasting
confidence: 99%
“…13) Among them, FGF21 is a hepatokine mainly expressed in the liver tissue. 10) Many studies have revealed FGF21 as a mediator of pleiotropic actions of PPARα. 18,19) Our previous study conducted in an obese mouse model revealed that MHY2013 increased FGF21 levels in the liver and serum.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In addition, it directly upregulates the expression of the hepatokine, fibroblast growth factor 21 (FGF21), which is considered a promising intervention target for metabolic diseases owing to its insulin-sensitizing and thermogenesis-inducing effects. 10) However, PPARγ is predominantly expressed in the adipose tissue, where it regulates adipocyte differentiation and insulin sensitivity. 7,8) PPARγ is a key regulator of adiponectin, a well-known insulin sensitizer.…”
Section: A Ppar Pan Agonist Mhy2013 Alleviates Age-related Hepatic Lmentioning
confidence: 99%
“…Amplifications of FGF19 in HCC have been reported in several genomics studies. 1,3,4 Recent studies have demonstrated that FGF19 plays key roles in hepatocarcinogenesis. 5 Genetic aberrations in FGF21 have not been reported in liver cancer genomics studies.…”
Section: Replymentioning
confidence: 99%
“…2 Interestingly, FGF21 was overexpressed in HCC. 1,3,4 It should be very interesting to assess if, from the data set of genome-wide analysis, HCC samples in which FGF19 high copy amplifications overlap with copy number variations or single mutations localized at 19q13.33 containing the FGF21 gene may emerge. This could be very relevant to understanding if an anti-FGF19 strategy may be potentially sufficient as a therapeutic approach.…”
mentioning
confidence: 99%